The impact of applying the servant leadership style among educators in educational institutes: A scoping review - Mohamad Rohieszan, Ramdan; Khoo, Yin Yin; Nur Yuhainis, Ab. Wahab; Norsamsinar, Samsudin; Nor Liza, Abdullah; Nurul Ashykin, Abd Aziz; Chamil Arkhasa Nikko, Mazlan; Norimah, Rambeli (UIKTEN - Association for Information Communication Technology Education and Science, 2024)
Leadership style is a critical concern in education amid technological shifts and paradigm changes. Despite extensive industry research, servant leadership remains underutilized in education, despite aligning with business education goals. This scoping review assesses the prevalence of servant leadership among educational leaders, offering insights into its feasibility, benefits, and challenges. Using the Web of Science (WoS), Scopus, and ERIC databases, the review compiles servant leadership research. Guided by Arksey and O'Malley's methodology, findings emphasize servant leadership's role in enhancing organizational effectiveness. They highlight behaviors as a prevailing theme, revealing limited background understanding. This insight aids educators in adopting effective leadership styles and exploring servant leadership's implications for educational leaders.